2004
DOI: 10.1897/03-362
|View full text |Cite
|
Sign up to set email alerts
|

Ammonium perchlorate effects on thyroid function and growth in bobwhite quail chicks

Abstract: Bobwhite quail chicks were used to investigate ammonium perchlorate (AP; NH4ClO4) effects on thyroid function and growth. Beginning at 3 to 4 d posthatch, we evaluated organismal thyroid status (circulating hormones), activation of the hypothalamic-pituitary-thyroid axis (thyroid wt) and thyroidal hormone content over a wide range of AP concentrations (50 microg/L - 4,000 mg/L) in drinking water, for relatively short (2-week) and longer (8-week) exposures. Thyroidal thyroxine (T4) content, the most sensitive i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 12 publications
3
40
1
Order By: Relevance
“…In addition, TDs present in small amounts in the environment may not cause overt changes of TH levels but may nonetheless alter hormonal homeostasis (Boas et al, 2006). A wellestablished example is perchlorate, which in small amounts does not alter circulating TH levels but diminished T4 content in the thyroid gland (Isanhart et al, 2005;McNabb et al, 2004a;McNabb et al, 2004b). These data agreed with in vitro studies which proposed an perchlorate-induced inhibition of sodium-iodide symporter (Tonacchera et al, 2004).…”
Section: Thyroid Disruptors Assayssupporting
confidence: 63%
“…In addition, TDs present in small amounts in the environment may not cause overt changes of TH levels but may nonetheless alter hormonal homeostasis (Boas et al, 2006). A wellestablished example is perchlorate, which in small amounts does not alter circulating TH levels but diminished T4 content in the thyroid gland (Isanhart et al, 2005;McNabb et al, 2004a;McNabb et al, 2004b). These data agreed with in vitro studies which proposed an perchlorate-induced inhibition of sodium-iodide symporter (Tonacchera et al, 2004).…”
Section: Thyroid Disruptors Assayssupporting
confidence: 63%
“…Intra-thyroidal T4 content, gene transcription activity and cellular growth appear to be more sensitive endpoints when assessing the significance of endocrine disruption from various chemicals. A well established example is perchlorate, which in small amounts does not alter plasma hormone levels, but diminishes thyroid gland T4 content (111)(112)(113), supporting the observation from in vitro studies of an inhibition of sodium -iodide symporter (NIS) (114). Thus, endocrine-disrupting chemicals present in small amounts in the environment may not cause overt changes of hormone levels in animals and humans, but may nonetheless alter the hormonal homeostasis.…”
Section: Mechanisms Of Actionmentioning
confidence: 77%
“…Studies of perchlorate exposure (perchlorate competitively inhibits thyroidal iodide uptake) in bobwhite quail have been used to compare the sensitivity of circulating thyroid hormone concentrations, thyroid gland weights and thyroid gland hormone content. These studies showed circulating hormones to be the most variable measurement and to be the least sensitive indicator of altered thyroid function (McNabb et al, 2004a(McNabb et al, , 2004b. At the lower and mid range concentrations of perchlorate, both high and low hormone concentrations were observed in different individuals and from experiment to experiment.…”
Section: Circulating T 4 and Tmentioning
confidence: 97%
“…Thus, in those cases where increased thyroid gland function cannot compensate, a cyclic pattern of decreases in circulating hormones and release of stored hormones can occur with resulting depletion of thyroid gland hormone stores. This type of cyclic pattern of responses occurs in response to iodine deficiency in humans (Delange and Ermans, 1996) and appears to be the case in both quail (McNabb et al, 2004a) and rats (York et al, 2001) exposed to perchlorate, which interferes with thyroidal iodide uptake. Such cyclic patterns of HPT axis response appear to be a key reason why measurements of plasma thyroid hormones often are highly variable in studies of endocrine disruption by chemicals (see "Circulating T 4 and T 3 ").…”
Section: Dynamic Relationships Among Levels Within the Hpt Axismentioning
confidence: 98%